IgG Glyco-Engineering to Improve IVIg Potency - Bruggeman, Christine W.; Dekkers, Gillian; Visser, Remco; Goes, Naneth W. M.; van den Berg, Timo K.; Rispens, Theo; Vidarsson, Gestur; Kuijpers, Taco W. (Frontiers in Immunology, 2018)
Intravenous immunoglobulins (IVIg) are used in the treatment of different autoimmune and inflammatory diseases, amongst which immune thrombocytopenia and hemolytic anemia. One of the modes of action of IVIg is preventing the phagocytosis of autoantibody-opsonized blood cells by saturation of the Fc-gamma receptors of macrophages in spleen and liver. IgG contains a fixed biantennary glycan at the asparagine residue at position 297 in the Fc tail. This glycan consists of a core structure of N-acetyl glucosamine (GlcNAc) and mannose groups, variably extended with core fucose, bisecting GlcNAc as well as end-standing galactose and sialic acid. This structural glycan influences the binding affinity of IgG to Fc-gamma receptors. By glyco-engineering, we generated monoclonal IgG antibodies with different Fc-tail glycans and tested both their opsonizing and blocking capacity in a phagocytosis assay of IgG-opsonized erythrocytes with human monocyte-derived macrophages. In contrast to a lack of effect in opsono-phagocytosis, these IgG glycovariants differentially inhibited the uptake of opsonized erythrocytes. The level of bisecting GlcNAc and galactosylation had unexpectedly larger impact than core fucosylation, and suggest that targeted modifications different from the core fucose may well improve the immunomodulating efficacy of IVIg treatment.